Multiphase well testing in bounded reservoirs - Mostafa Reda Sanad; Ahmed Hamdy Elbanbi; Eissa Mohamed Shokier; Elsayed Ahmed Eltayeb (Cairo : Mostafa Reda Sanad, 2021)
Well testing in gas and multi-phase (Volatile oil & Gas condensate) reservoirs cannot be analyzed in the same way of oil reservoirs as the gas properties and phases saturations and properties are functions of reservoir pressure. using pseudo-time and pseudo-pressure functions for gas and multiphase systems considers the properties variation and gives an equivalent incompressible fluid behavior. This is a comprehensive study of applying different types of time functions (Real time, Agarwal pseudo-time and Fraim pseudo-time) on dry gas and multiphase systems to conclude guidelines to help to determine the most suitable time function that gives most accurate value of certain well test parameter under certain reservoir boundary condition for both of dry gas and multiphase systems
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Metallurgical Engineering
Issued also as CD
Keywords: Agarwal; Bounded Reservoirs; Multiphase